PENGEMBANGAN SISTEM OJRS+ (ONLINE JADWAL RENCANA STUDI PLUS) SEBAGAI MEDIA PERENCANAAN JADWAL KULIAH - Muhamad Yusup; Ary Budi Warsito; Ninu Apriyani (CCIT Journal, 2016)
OJRS at the College of Raharja is an information system that is in the component of the SIS (Student Information System). OJRS present to facilitate students in performing void add class schedules and print the form - the form that is in the menu OJRS. OJRS main function is to facilitate the process of void-added service class schedule resulting in fast and accurate data. Starting from the view class schedules, add and cancel courses, pick up class schedules to generate report output in the form of KSTF (Final Fixed Study Card) for students. This research is a quantitative research design using survey research using questionnaires processing techniques are processed based on validity and reliability test using SPSS software. With research results OJRS system is running is still relatively less than the maximum, and still there are 5 (five) deficiencies or weaknesses in the system. Therefore, in this study will be explained about the system OJRS ongoing at this time to describe the analysis of the system using UML (Unified Modeling Language) diagrams and try to provide input in the form of system design to support and contribute to the development of systems OJRS + that are in SIS + (Student iLearning Services) which can be accessed online outside the campus environment easily and quickly just by using the Internet connection